Reclaiming the Faravahar: Zoroastrian Survival in Contemporary Tehran, by Navid Fozi - Khaira, Arshdeep (Religious Studies and Theology, 2016)
Reclaiming the Faravahar: Zoroastrian Survival in Contemporary Tehran, by Navid Fozi. Iranian Studies Series. Leiden University Press, 2014. 240pp. 9 halftones, | 1 illustration, 1 table. Pb. 26.29. ISBN-13: 9789087282141.